Does environmental degradation influence migration? The case of Malaysia and Asia-Pacific countries - Ow, Wilson Chee Seong; Abdul Hamid, Baharom; Habibullah, Muzafar Shah (School of Social Sciences, Universiti Sains Malaysia, 2012)
The purpose of this study is to determine the significant linkages between migration (both emigration and immigration) and environmental degradation. We employed cross-sectional analysis to investigate the relationship by employing data on immigration and emigration. As for economic condition we employed macro-variables such as environmental degradation (CO2 emission), real income (real Gross Domestic per capita), price level (consumer price index) and distance among the countries. Two different points of time were regressed cross-sectionally, with White standard being employed to remove traces of heterogeneity, albeit, 1990 and 2000. Results clearly indicate that as forecasted, the chosen variables indeed have significant relationship with migration. The results provide some evidence on the important role played by these variables in influencing migration.